Fine tuning for totally endoscopic mitral valve surgery: ERAS applications - Ertugay, Serkan; Karaca, Sedat; Engin, Ayşen Yaprak; Kahraman, Ümit; Ünlü, Zehra; Kocabaş, Seden; Çalkavur, Tanzer; Özbaran, Mustafa (Frontiers in Cardiovascular Medicine, 2024)
Aim One of the philosophies of minimally invasive mitral surgery is to enhance recovery after surgery (ERAS). Beyond surgical applications, ERAS applications provide a complementary approach to optimize postoperative course and discharge. In this report, we aim to present institutional protocol for ERAS and its results in patients who underwent totally endoscopic mitral valve surgery (TEMVS). Patients and methods Between 2021 and 2023, totally 113 patients who underwent TEMVS were included in this study. TEMVS was performed by peripheral cannulation and 3D endoscopic technique. As a dedicated team, institutional ERAS protocols which are used are listed above: (1) Education; operative course, cessation of smoking and alcohol. (2) Anemia; diagnostic evaluation and its treatment by iv iron. (3) Optimization of blood glucose; checking of HbA1c and control of hyperglycemia. (4) Rehabilitation; Physical and pulmonary rehabilitation. (5) Anxiety and Analgesia treatment. (6) Blood Conservation techniques; Antifibrinolytic, acute normovolemic hemodilution, less priming volume, mini-incision, meticulous surgery by 3D endoscope. (7) Postoperative; early extubation, prevention of nausea, aggressive analgesia, early mobilization, early removal of tubes. (8) Restrictive transfusion strategy. (9) Early discharge. Results The mean age was 54.7 years, and 56% was female. The rate of iv iron therapy for anemia was 26.5%. Mitral repair was performed in 58.4% of the cases. The repair rate of degenerative mitral valve was 96.9%. Of all, 68.1% did not have any red packed cells and 15.9% had only one unit. Ninety-five patients (90.2%) did not have any unit of fresh frozen plasma. The median extubation time was 7 h. On the postoperative first day, 96% of foley catheters, 87% of all central venous catheter and 93% of all drainage tubes are removed. The rates of respiratory, infectious, and renal complications were 9%, 3.5%, 3.4% respectively. The median ICU, and hospital stays were 1 and 5 days respectively. There was only one mortality in the early postoperative period. Conclusion Totally endoscopic mitral valve surgery provides minimal surgical trauma. By the addition of well-established and nurse-based ERAS protocols, complication and transfusion rates can be decreased, early recovery and discharge can be provided.